Development of a User-friendly Tool for Groundwater Wellfields Management - Alqadi, Mohammad; Aldwairi, Ala; Margane, Armin; Brueckner, Florian; Schneider, Michael; Merchán-Rivera, Pablo; Chiogna, Gabriele (Proceedings of the IAHR World Congress, 2022)
Most studies in the field of groundwater management focus on regional management of ground water resources, and only a few focus on monitoring individual wells in terms of improving the management system and applying effective well field management plans. The lack of reliable monitoring systems hinders the proper management, planning, maintenance, and operation of wells, which consequently increases the management and operational costs and could add additional pressure on the water resource. Several tools have been developed to manage groundwater resources; however, there is not a specific software that comprehensively tackles all groundwater management aspects on well and well field levels. This research aims to develop a user-friendly Decision Support Software and Database for Well field Management (DeMa) that aids the decision making process surrounding the management and operation of the wells, which will be a continuation of the work conducted in Alqadi et al., (2019). The software is divided into four modules (i) Database Management Tool (DbMT) (ii) Observation Based tool (OBT) to visualize the database in graphs, (iii) Research Based tool (RBT), which is a user-friendly tool to help well field managers to apply novel research methodologies to the user study area, and (v) Documents Management Tool (DMT) to manage all documents related to the wells. The software is conceived in a modular way, such that it can be enriched by plugging-in additional tools and options in subsequent versions. Future developments include water quality analysis and well rehabilitation support with the aim of creating an all-encompassing tool that meets the well field manager needs.
CRIS-Team Scopus Importer:2024-04-17
Keywords: Borehole; Groundwater Management; Software Development; Tool Development; Well field Management